Right in their own eyes: the Gospel according to the Book of Judges - Schwab, George M. (The Gospel according to the Old Testament, 2011)
Juggling Judges -- Significative stylization -- Authors' agendas -- A keen Kenite -- Soiled southpaw, rotund ruler -- Does Yahweh command jihad? -- The sissy, the sisters, and Sisera -- Mastering Midian -- Abominable Abimelech -- Minor magistrates -- Jephthah's jaundice -- Philistine foxes -- Dan's dirty dealings -- Benjamin's baleful bent